INTERACTIVE MULTIMEDIA STORYBOOK FOR PRE SCHOOLERS: READING FOR FUN WITH ANNA - Bakar, Norasiken; Wan Husain, Wan NurLiyana; Husain, Kalthom (Journal of Human Capital Development (JHCD), 2013)
An effective reading for Fun with Anna is an interactive storytelling learning method for children to develop their vocabulary knowledge by exploring many things using their imagination. The objectives of this paper include to develop interactive storybook that focus on vocabulary, helps children recognize vocabulary by giving them graphics to imagine, to identify multimedia elements and to conduct an effectiveness testing on interactive storybook. The interactive multimedia story book was developed based on ADDIE model that is the basic term for the five phase instructional design model consisting of Analysis, Design, Development, Implementation and Evaluation. The effectiveness testing reading for fun with Anna was conducted based on the Pre and Post testing through a case study of a Kindergarten in Melaka, Malaysia. The findings showed that the Post-Test result, who underwent the teaching and learning process using the reading for fun with Anna had a higher achievement level in comparison with the Pre-Test, who experienced the conventional approach to teaching and learning. This paper implies the effectiveness of the reading for fun with Anna in classroom. For future work, it is recommended that the student’s score should record after children do their exercises. The score will be appearing and they can save it under their name. This can build competitive feelings in them to compete with others indirectly it will motivate them to do better